2023
DOI: 10.1212/wnl.0000000000207749
|View full text |Cite
|
Sign up to set email alerts
|

Common Pathways of Epileptogenesis in Patients With Epilepsy Post–Brain Injury

Shubham Misra,
Erum I. Khan,
TuKiet T. Lam
et al.

Abstract: Background and Objective:Epilepsy may result from various brain injuries, including stroke (ischemic and hemorrhagic), traumatic brain injury, and infections. Identifying shared common biological pathways and biomarkers of the epileptogenic process initiated by the different injuries may lead to novel targets for preventing the development of epilepsy. We systematically reviewed biofluid biomarkers to test their association with the risk of post-brain injury epilepsy.Methods:We searched articles until January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“… 9 Although these analyses indicated the plausible role of inflammation in epileptogenesis, inflammation is likely not the only mechanism: methodological heterogeneity, bias, and insufficient validation of biomarkers were noted in the reported studies; therefore, more longitudinal studies are critically needed. 9 …”
Section: Risk Factorsmentioning
confidence: 97%
See 2 more Smart Citations
“… 9 Although these analyses indicated the plausible role of inflammation in epileptogenesis, inflammation is likely not the only mechanism: methodological heterogeneity, bias, and insufficient validation of biomarkers were noted in the reported studies; therefore, more longitudinal studies are critically needed. 9 …”
Section: Risk Factorsmentioning
confidence: 97%
“…In a comprehensive systematic review, 15 blood and 7 CSF biomarkers were significantly associated with post-brain injury epilepsy. 9 Enrichment analysis identified that the significant biomarkers (IL-6 and IL-1β) were predominantly associated with inflammation. 9 Although these analyses indicated the plausible role of inflammation in epileptogenesis, inflammation is likely not the only mechanism: methodological heterogeneity, bias, and insufficient validation of biomarkers were noted in the reported studies; therefore, more longitudinal studies are critically needed.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Bioinformatics offers opportunities to assess the biofluid biomarkers of epileptogenicity. 6 Analysis of these multidimensional data to build a COSY prediction model is now possible, thanks to advances in computational neurosciences.…”
Section: Nishant K Mishramentioning
confidence: 99%